Article – Speaking the Unspeakable? Nicola Lacey’s Unspeakable Subjects and Consent in the Age of #MeToo - Cooper, Chiara (feminists@law, 2018)
In the midst of the #MeToo movement, a woman named Grace came forward describing an experience – that she had labelled sexual assault – with actor/comedian Aziz Ansari. This encounter did not reflect a clear and dichotomous giving or withholding of consent in line with a yes or no to sex. Because of this ambiguity, Grace’s assault became somewhat of a catalyst for #MeToo. The movement was divided into critics on the one hand, who argued her evening with Ansari was no more than an episode of bad heterosex, and supporters on the other, for whom Grace’s account resonated and who subsequently backed the need for deeper conversations on the topic of sexual consent. Considering these debates and Grace’s experience, this paper looks to the work of Nicola Lacey in Unspeakable Subjects to analyse how current ideas of sexual consent, in the 2003 Sexual Offences Act and beyond, fail to reflect a nuanced understanding of sexual harms, consequently neglecting ambiguous experiences in heterosex – like Grace’s – of consented to unwanted sex. Through an exploration of Lacey’s concept of sexual integrity, scholarship in the area of BDSM and other sociolegal approaches to considering consent and sex more ethically, this paper advocates expanding our view of consent to involve a critical analysis of how multiple power dynamics can intersect to affect individuals’ abilities to freely and meaningfully consent in heterosex.